An infectious bronchitis virus Mass-like strain from Brazil causing kidney damage and tropism in a broiler flock - Fernando, Filipe Santos [UNESP]; Kasmanas, Thaiane Coelho [UNESP]; Lopes, Priscila Diniz [UNESP]; Montassier, Helio José [UNESP]; Assayag, Mário Sérgio (Wiley, 2017)
In this case, the authors showed an infectious bronchitis virus (IBV) strain from Massachusetts (Mass) genotype with nephropathogenic characteristics. This virus has great importance for causing damage to poultry production related to feed conversion, association with secondary infections and carcass condemnation in the slaughterhouse. IBV comprises several genotypes, and among these genotypes some pathogenic characteristics are specific, such as the strong pathogenesis of some Mass strains for the respiratory tract. However, the authors isolated IBV/Brazil/NUP/0316 strain and showed that when isolated from broilers it causes mild to moderate renal damage, besides presenting high amino acid sequence identity with other pathogenic strains isolated in countries far from Brazil.